Organizational Commitment As Moderating The Relationship Between Anticipatory Socialization And Whistleblowing Intention - Imam Abu Hanifah; Vierina Clyde (International Journal of Social Service and Research, 2022)
This study aims to determine the effect of organizational commitment as moderating the relationship between anticipatory socialization and whistleblowing intention. The sample technique used was purposive sampling. The population were all 87 Government Internal Supervisory Apparatus (APIP) at the Inspectorate of Banten Province. Structural Equation Model using Partial Least Square statistical software was used to analyze the data. The result of this study indicates that anticipatory socialization partially has a positive significant relationship on the whistleblowing intention and commitment organization was able to moderate the relationship of anticipatory socialization and whistleblowing intention.